A dynamic IS-LM model with relaxation oscillations. Issue 3 (3rd March 2016) - Volná, Barbora
Abstract : In this paper, we show the existence of relaxation oscillations in the economy. For description of macroeconomic situation, we use the fundamental equilibrium model called IS-LM model.